The value of pyrans as anticancer scaffolds in medicinal chemistry. Issue 59 (25th July 2017) - Kumar, Dinesh; Sharma, Pooja; Singh, Harmanpreet; Nepali, Kunal; Gupta, Girish Kumar; Jain, Subheet Kumar; Ntie-Kang, Fidele
Abstract : Pyran-based heterocycles are promising for anticancer drug discovery. Abstract : Pyran is an oxygen-containing heterocyclic moiety, which exhibits an array of pharmacological properties. Pyran is also one of the important structural subunits found widely in natural products, e.g. coumarins, benzopyrans, sugars, flavonoids, xanthones, etc. The diverse anticancer capabilities of pyrans have been additionally evidenced by the fact that this heterocycle has recently been a focal point for researchers worldwide. This review provides a summary of pyran-based anticancer compounds, with emphasis on the past 10 years. It focuses on advancements in the field of naturally occurring pyrans as anticancer agents. The discussion also includes structure–activity relationships, along with the structures of the most promising molecules, their biological activities against several human cancer cell lines, as well as mechanistic insights discovered through the pharmacological evaluation and molecular modeling of pyran-based molecules. The promising activities revealed by these pyran-based scaffolds undoubtedly place them at the forefront for the discovery of prospective drug candidates. Thus, they could therefore be of great interest to researchers working on the synthesis of antitumour drug candidates.